Degos disease with multiple intestinal perforations: A missed-opportunity case report and literature review - Ai, Wen; Liang, Zhihua; Li, Feng; Yu, Haihua (Frontiers in Cardiovascular Medicine, 2022)
Introduction Degos disease, also known as malignant atrophic papulosis (MAP), is a rare systemic obstructive vascular disease with unknown pathophysiology, which can affect multiple systems, especially gastrointestinal tract and central nervous system. Intestinal perforations with MAP is associated with high mortality rate and ambiguous treatment outcomes. Case presentation Here we report a missed-opportunity case of Degos disease characterized by generalized skin eruption and multiple intestinal perforations. Definite diagnosis of Degos disease was finally concluded after two exploratory laparotomy operations and skin biopsies. Due to the delayed diagnosis and treatment, the patient died after being discharged automatically in spite of application of aspirin and low-dose subcutaneous heparin. In view of such circumstances, we searched the Pubmed using “Degos [Title] OR Malignant Atrophic Papulosis [Title]” AND “perforation [Title] OR perforations [Title]” and make a detailed analysis of the result. Conclusions Degos disease is a rare systemic obstructive vascular disease with unknown pathologic mechanism and unavailable treatment methods. Diagnosis is usually based on the presence of pathognomonic skin lesions and tissue biopsy. Gastrointestinal involvement can cause serious and lethal conditions with high mortality. Currently, how to achieve a satisfying prognosis of MAP with intestinal perforations becomes the most urgent problem in front of medical staff.